The ancient iron mines of Meroe. Issue 3 (3rd July 2018) - Humphris, Jane; Bussert, Robert; Alshishani, Fareed; Scheibner, Thomas
ABSTRACT: Ongoing archaeometallurgical research at the Royal City of Meroe and the nearby Meroitic town of Hamadab in Sudan has established the presence of a Kushite iron production tradition spanning over one thousand years. Potentially from as early as the seventh century BC to as late as the sixth century AD, a significant quantity of iron was produced at Meroe, while Hamadab appears to have started producing iron during the latter stages of this time-frame. Previous investigations assumed that the iron ore exploited for use was widely available and easily accessible, close to the ancient city itself. This paper presents the results of archaeological and geological research that has, for the first time, identified ancient iron mining activity in the area. Insights gained into certain aspects of the ore procurement stage of the chaîne opératoire of Meroitic iron production, including the nature of the mined ores and the manner in which this activity was conducted, are presented. Indications as to the organisation of mining activities are also provided. The significant potential of this avenue of research is highlighted and potential future research questions are posed.